Indonesian collaborative governance analysis facing Free Papua movement - ANRIANI, S.; RAHAYU, A.Y.S.; SALOMO, R.V. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The purpose of this study is to analyze the conflict management that has been carried out by the government through the integrative framework of Collaborative Governance. The research method used was the deductive Post-Positivist paradigm by collecting data through interviews, focus group discussions, and surveys regarding the implementation of Special Autonomy Policy. The results of the study based on the integrative framework of collaborative governance model showed that the process of collaboration in implementing the Special Autonomy policy has not been successful and is less effective. RESUMEN El propósito de este estudio es analizar la gestión de conflictos que ha llevado a cabo el gobierno a través del marco integrador de la Gobernanza Colaborativa. El método de investigación utilizado fue el paradigma deductivo post-positivista mediante la recolección de datos a través de entrevistas, discusiones de grupos focales y encuestas sobre la implementación de la Política de Autonomía Especial. Los resultados mostraron que el proceso de colaboración en la implementación de la Política Especial de Autonomía no ha sido exitoso y es menos efectivo.